As auditorias militares no aparato repressor do regime ditatorial (1965-1968) - Wanderley, Erika Kubik da Costa (2009)
The central objective of this research is to understand the relations established between the first instance of the Brazilian Military Justice the military audits and the repressive apparatus built by the Brazilian military regime in the period of institutionalization that starts with the edition of the second Institutional Act, in October of 1965 and finishes with the publication of the fifth Institutional Act, in December of 1968. The choice of this organ as an object of investigation is essentially, due to its importance in the legal architecture of the regime, mainly after the alterations established by the second Institutional Act, that transferred to the Military Justice the competence to prosecute and judge civil accused of crimes against the national security. The main analytic focus concentrated in the political judgments realized by this instance and the empirical material consisted essentially in primary fonts, of documentary character.